Ehlers-Danlos Syndrome associated with cardiomyopathy hypertrophic obstructive - Raimundo José Almeida de Oliveira Pinto; Adaílton Araújo dos Santos; Mablo de Castro Azevedo; Saulo Sacramento Meira (Sociedade Brasileira de Dermatologia, 2015)
AbstractEhlers-Danlos syndrome is a rare clinical condition caused by a genetic change that results in the formation of structurally or functionally altered collagen. The clinical manifestations are varied, being the most obvious skin hypermotility and increased joint flexibility, although other systems - such as cardiovascular, respiratory and neurological - may also be affected. This paper presents the report of a patient who sought medical attention with complaints of atypical chest pain. Clinical evaluation enabled hypothetical diagnosis of hypertrophic obstructive cardiomyopathy and Ehlers-Danlos syndrome. Initial electrocardiogram, echocardiogram and 24 hours holter allowed the confirmation of the first hypothesis. A skin biopsy performed later associated clinical data and confirmed the second hypothesis.